Ideological traditionalism and organisational innovation in Greek Orthodox ecclesiastical governance. Issue 3 (1st September 2020) - Patrikios, Stratos
ABSTRACT: Studies of church governance approach religious change either as 'soft' transformation (ideological and discursive adjustments implemented by clerical élites) or as 'hard' restructuring (shifts in organisational decision-making processes and administrative forms). This article illustrates that the joint, rather than separate, consideration of the two types of change provides a more nuanced description of the internal dynamics of religious organisations. Employing a framework with comparative applicability, which breaks with standard theoretical approaches, the empirical application examines a case in which the two types of change coincided: the Orthodox Church of Greece in the late twentieth century, where a radically conservative ideological transformation accompanied a particular instance of bureaucratic modernisation (lay involvement in high-level ecclesiastical governance).